199k views
2 votes
If f(x) = 3x-2 and g(x) = 2x + 1, find (f-g)(x)​

If f(x) = 3x-2 and g(x) = 2x + 1, find (f-g)(x)​-example-1
User Allkin
by
5.4k points

2 Answers

5 votes

Answer:

D.
x-3

Explanation:


f(x) = 3x-2


g(x) = 2x + 1


(f-g)(x)


f(x)-g(x)


(3x-2)-(2x+1)


3x-2-2x-1


3x-2x-2-1


1x-3

User ChrisPhoenix
by
5.9k points
3 votes

Answer:

x-3

Explanation:

f(x) = 3x-2

g(x) = 2x + 1

(f-g)(x) = 3x-2 - ( 2x+1)

Distribute the minus sign

=3x-2 -2x-1

Combine like terms

= 3x-2x -2-1

=x-3​

User Mohikhsan
by
5.4k points